'They said, let's teach you how you are going to care for the child at home...': caregivers' and healthcare worker's perceptions and experiences of post-discharge preterm care in eastern Uganda - Holly Lyne; Kathy Burgoine; Collin Ogara; James Ditai; Melissa Gladstone (BMC, 2022)
Abstract Background Complications of prematurity are the leading cause of neonatal mortality, and the majority of these deaths occur in low and middle-income countries. Research in these settings has focused on improved outcomes for preterm infants in hospital settings, however, research into the continuation of preterm care in the home after discharge from a neonatal unit is limited. This study examines the experiences and perceptions of caregivers of preterm infants during the initial weeks following discharge from a neonatal unit in Uganda, and the views of healthcare workers (HCWs) on the ability of caregivers to cope. Methods This qualitative study used multiple data collection approaches, namely focus group discussions (FGDs), in-depth interviews (IDIs), field observations, and case studies to explore the perceptions and experiences of providing care to preterm infants post-discharge from a neonatal unit in eastern Uganda from the perspectives of caregivers and HCWs. Results We recruited 39 participants with a total of 35 separate sessions including 18 IDIs (12 caregivers and 6 HCWs), 3 FGDs (17 caregivers), and 4 case studies (14 separate IDIs over 5 weeks after discharge, three mothers, and one grandmother). IDIs and FGDs took place at the Mbale Regional Referral Hospital or in participants' homes. Key themes emerged; preparation for continuing care in the home, psychosocial challenges to providing preterm care in the home, barriers to continuing preterm care in the home, and suggestions for improvement of preterm care in the home. Caregivers had good knowledge and awareness about different aspects of preterm care. Following discharge, caregivers struggled to maintain quality care due to loss of continuous support from the neonatal team, feelings of anxiety and isolation, financial issues, and home responsibilities. Conclusion This study highlights multiple challenges to continuing preterm care in this Ugandan setting. Improved training and education for caregivers, especially in neonatal resuscitation, enhanced and continued support of the caregiver and infant in the home, and increased community involvement following discharge may all be key solutions. These findings are fundamental to improving care in the home for preterm infants in eastern Uganda and similar settings.